Effect on Physical and Mechanical Properties of Conventional Glass Ionomer Luting Cements by Incorporation of All-Ceramic Additives: An In Vitro Study. (30th September 2020) - Saran, Runki; Upadhya, Nagraj P.; Ginjupalli, Kishore; Amalan, Arul; Rao, Bharath; Kumar, Saurabh
Abstract : Introduction . Glass ionomer cements (GICs) are commonly used for cementation of indirect restorations. However, one of their main drawbacks is their inferior mechanical properties. Aim . Compositional modification of conventional glass ionomer luting cements by incorporating two types of all-ceramic powders in varying concentrations and evaluation of their film thickness, setting time, and strength. Material & Methods . Experimental GICs were prepared by adding different concentrations of two all-ceramic powders (5%, 10, and 15% by weight) to the powder of the glass ionomer luting cements, and their setting time, film thickness, and compressive strength were determined. The Differential Scanning Calorimetry analysis was done to evaluate the kinetics of the setting reaction of the samples. The average particle size of the all-ceramic and glass ionomer powders was determined with the help of a particle size analyzer. Results . A significant increase in strength was observed in experimental GICs containing 10% all-ceramic powders. The experimental GICs with 5% all-ceramic powders showed no improvement in strength, whereas those containing 15% all-ceramic powders exhibited a marked decrease in strength. Setting time of all experimental GICs progressively increased with increasing concentration of all-ceramic powders. Film thickness of all experimental GICs was much higher than the recommended value for clinical application. Conclusion . 10% concentration of the two all-ceramic powders can be regarded as the optimal concentration for enhancing the glass ionomer luting cements' strength. There was a significant increase in the setting time at this concentration, but it was within the limit specified by ISO 9917–1:2007 specifications for powder/liquid acid-base dental cements. Reducing the particle size of the all-ceramic powders may help in decreasing the film thickness, which is an essential parameter for the clinical performance of any luting cement.